A new genus of Eurrhacini from the Brazilian Atlantic Forest (Coleoptera: Lycidae: Lycinae) with an updated key to genera - Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2023)
Atlanticolycus gen. nov., is herein described as a new genus of Neotropical Lycidae in the Eurrhacini tribe. Five new species are described: Atlanticolycus camposgerais sp. nov., A. japi sp. nov., A. itatiaia sp. nov., A. ilhabela sp. nov., and A. morretes sp. nov., all distributed in Brazilian Atlantic Forest. Illustrations of diagnostic characters, a key for species identification and a key to genera of Eurrhacini with flabellate antennae are presented.